Irkutskgrazhdanproject – 50 - Grigoryeva, Elena (project baikal, 2015)
Irkutskgrazhdanproject celebrates its anniversary. It has been working for the good of the city and the region for half a century. Within 50 years it has created dozens of microdistricts in Irkutsk and other towns of the region, millions of square meters of housing, hundreds of cultural, educational, commercial and personal service facilities. And a number of outstanding architectural and town-planning works, which have received professional, public and national recognition.They were created by several generations of highly qualified specialists, architects and engineers. While working simultaneously on a dozen of projects, they taught and brought up young specialists, sharing their knowledge and experience in designing for a changeable climate, high seismicity and a historical city. The Institute became a source of manpower: together with design as its main activity, it also offered internship and advanced training. Now this manpower, graduates from the Institute, work at the best design companies of the city.The authors of this issue are representatives of several generations of the Institute’s staff. Their recollections and personal photo records made it possible to chronologize some episodes from Irkutskgrazhdanproject everyday life and to feel the atmosphere of creativity and intelligence.The history of the Institute is roughly divided into periods. Neither this history nor its description in the issue has strict boundaries. However, the role of certain personalities in this history is so great that one may say that it was they who made Irkutskgrazhdanproject so that we are proud of it, we love it and devote many years and decades of our lives to it.
Keywords: Irkutskgrazhdanproject; microdistricts; Irkutsk; architecture; town planning